Role of flowcytometry in atypical lymphocytosis - Kullar, Rashan; Tripathi, Preeti; Mishra, Kundan; Venkatesan, S.; Bhatia, Jasvinder Kaur (International Journal of Advances in Medicine, 2024)
Infectious mononucleosis (IM) is a benign condition defined by lymphomononuclear cell proliferation. Symptoms range from a vague constitutional syndrome to fever, rash, jaundice, hepatosplenomegaly, lymphadenopathy, and in rare cases, autoimmune hemolytic anemia. The viruses responsible for this syndrome are EBV (the most prevalent), CMV, HIV, Hepatitis virus, Adenovirus, and others. Because the virus mostly impacts lymphomononuclear cells and the reticuloendothelial system, it may trigger intense lymphoproliferation, leading to uncommon manifestations in peripheral smear. These can be misdiagnoses as leukemia/lymphoma. The clinical profile of a brief history, mild organomegaly, and peripheral smear morphology commonly overlaps. This pitfall in the diagnosis can lead to ineffective treatment. Immunophenotyping by flowcytometry or immunohistochemistry, a mono-spot test, and specific viral ag/ab assays are required for a correct diagnosis. Flowcytometry profiles are not always adequate to rule out neoplastic proliferations. We provide a case study of a young teenage boy who arrived with an abrupt history of low-grade fever, hepatosplenomegaly, cervical lymphadenopathy, elevated leukocyte count, and atypical lymphoid cells on peripheral smear. What was previously thought to be a hematological malignancy was discovered to be a self-limiting acute IM (CMV caused), and the patient was discharged after a brief course of treatment.